Optimizing the reaction pathway of methane photo-oxidation over single copper sites - Chengyang Feng; Shouwei Zuo; Miao Hu; Yuanfu Ren; Liwei Xia; Jun Luo; Chen Zou; Sibo Wang; Yihan Zhu; Magnus Rueping; Yu Han; Huabin Zhang (Nature Communications)
Abstract Direct photocatalytic conversion of methane to value-added C1 oxygenate with O2 is of great interest but presents a significant challenge in achieving highly selective product formation. Herein, a general strategy for the construction of copper single-atom catalysts with a well-defined coordination microenvironment is developed on the basis of metal-organic framework for selective photo-oxidation of CH4 to HCHO. We propose the directional activation of O2 on the mono-copper site breaks the original equilibrium and tilts the balance of radical formation almost completely toward •OOH. The synchronously generated •OOH and •CH3 radicals rapidly combine to form HCHO while inhibiting competing reactions, thus resulting in ultra-highly selective HCHO production (nearly 100%) with a time yield of 2.75 mmol gcat −1 h−1. This work highlights the potential of rationally designing reaction sites to manipulate reaction pathways and achieve selective CH4 photo-oxidation, and could guide the further design of high-performance single-atom catalysts to meet future demand.